Rantai Pasok Beras di Kabupaten Tanjung Jabung Timur - Elwadinata, Frenco; Napitupulu, Dompak; HD, Ernawati (Jurnal MeA (Media Agribisnis), 2024)
East Tanjung Jabung District is one of the rice barns in Jambi Province, with rice production in 2022 reaching 24,562 tons of GKG, making it the 3rd largest district in rice production in Jambi Province. However, the district faces several problems related to the rice supply chain, such as long supply chains and poor information flow due to inadequate infrastructure. This study aims to understand the rice supply chain mechanism in East Tanjung Jabung Regency. A descriptive analysis method using the Food Supply Chain Network (FSCN) approach was used in this study. Farmers were randomly sampled to obtain 72 farmers, while traders were sampled using the snowball sampling method. The results show that the majority of rice production in this district is aimed at meeting local and out-of-region markets, with development targets including increased production and distribution. The supply chain structure involves farmers, village intermediaries, rice mills, district intermediaries, and retailers. They select partners based on price, experience, personal relationships, trust, and information disclosure. Agreements between farmers and traders are informal, while the government provides support through various programs and assistance. Transactions in the supply chain are conducted in cash. Farmers, rice millers, and traders have resources. There are six patterns of supply chain channels, with smooth financial flows, but barriers to product and information flows.